2011
DOI: 10.1021/es102151w
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of PAHs from Indoor Crop Residue Burning in a Typical Rural Stove: Emission Factors, Size Distributions, and Gas−Particle Partitioning

Abstract: Indoor combustion of crop residues for cooking or heating is one of the most important emission sources of polycyclic aromatic hydrocarbons (PAHs) in developing countries. However, data on PAH emission factors (EFs) for burning crop residues indoor, particularly those measured in field were scarce, leading to large uncertainties in the emission inventories. In this study, EFs of PAHs for nine commonly used crop residues burnt in a typical Chinese rural cooking stove were measured in simulated kitchen. The meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
142
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 222 publications
(176 citation statements)
references
References 43 publications
20
142
2
Order By: Relevance
“…Similar results were also found for PAHs freshly emitted from wood combustion [45] and indoor crop residue burning [46]. Some reports showed that adsorption on diesel soot (mainly elemental carbon) also plays an important role in partitioning of PAHs in urban atmosphere influenced by vehicular emission [47,48].…”
Section: Gas-particle Distribution Of Pahssupporting
confidence: 78%
“…Similar results were also found for PAHs freshly emitted from wood combustion [45] and indoor crop residue burning [46]. Some reports showed that adsorption on diesel soot (mainly elemental carbon) also plays an important role in partitioning of PAHs in urban atmosphere influenced by vehicular emission [47,48].…”
Section: Gas-particle Distribution Of Pahssupporting
confidence: 78%
“…Also, it is important to note that although our results indicate that the proportion of solid-fuel users decreased from 1991 to 2012, since the overall population in China increased significantly (from 1.16 billion in 1991 to 1.35 billion in 2012), the absolute number of people using solid fuels was still extremely large (Table S2). This suggests that a significant number of people are potentially exposed to harmful pollutants, and consequently at high risk for the development of disease, as inefficient burning of solid fuels often yield a large number of incomplete pollutants [18][19][20].…”
Section: Hfu For Cooking and Temporal-spatial Distributionmentioning
confidence: 99%
“…They mainly result from incomplete combustion of carbon-containing materials and can partition between the gas and the particulate phase (Fernán-dez et al, 2002;Hytönen et al, 2009;Shen et al, 2011). This partitioning process strongly depends on particle sizes, PAH species and temperature, and it affects PAH transport, deposition, and degradation as well as health impacts.…”
Section: Introductionmentioning
confidence: 99%